PENGARUH WAKTU REAKSI DAN WAKTU TINGGAL STABILISASI PADA SEQUENCING BATCH REACTOR AEROB DENGAN PENAMBAHAN KARBON AKTIF TERHADAP PENURUNAN CHEMICAL OXYGEN DEMAND - Hadiwododo, Mochtar; Junaidi, Junaidi (Universitas Diponegoro, 2007)
Sequencing Batch Reactor (SBR) process represent biological wastewater treatment with aerobic process used occasionally to eliminate dissolve organic materials constructively microorganism especially bacterium in course of organic degradation. Sequencing Batch Reactor(SBR )has five phase in its cycle, namely fill, react, setlle, draw and iddle phase. In this study iddle phase was changed into stabilization phased where microorganism oxydize organic matter as stored materials in cell under certain aeration period of time.The objectives of this research are to know influence of time react and time stabilisation with added of Granular Active Carbon (GAC) to COD removal. In research was used reactor from plastic material with diameter 25 cm and high is 25 cm, volume of wastewater in reactor is 5 liter and volume of sludge is 35% from volume of wastewater that 1,75 liter. Waste that used was artificial waste glucose soluble with 1032.5 mg/l concentration of COD. As independent variable are react time: (0,5 ; 1; 1,5 ; 2 hours) and stabilitation time (3; 4; 5; 6 hours), if dependent variable are removal of carbon. Application of Granular Active Carbon (GAC) as absorbent, combined with suspended system of SBR, is expected to be able to remove COD better. As the result this research shows that the finest of carbon removal is occurred in time react 1 hours, andtime stabilitation 6 hours is 97.23%. COD removal with GAC better than that without GAC.